METAMORPHIC ANALYSIS IN SONG LYRICS BATAK TOBA â€œAUT BOI NIANâ€ WRITTEN BY WERVIN PANGGABEAN - Simanjuntak, Marudut Bernadtua (JOURNAL OF ADVANCED ENGLISH STUDIES, 2021)
This study aims to analyze the metamorphic sentences contained in a folk song which is popular in Indonesia. "Aut Boi Nian" is a song of Batak Toba literature written by Wervin Panggabean. This song has been widely played both in large-scale concerts, popular movie soundtracks and the number of shows that exceed 10 million views on the youtube channel. The meaning of the metamorphic sentence in this song contains the values of the Batak Toba culture which are represented in metamorphic sentences which when analyzed have very deep meaning, both in terms of the meaning of translation, cultural culture and moral message. The lyrics of this song were created in accordance with emotional expressions that even represented the existence of Bataknese men in general.